Linking Teacher–Learner Discourse With Mathematical Reasoning of Students With Learning Disabilities: An Exploratory Study. (February 2020) - Xin, Yan Ping; Chiu, Ming Ming; Tzur, Ron; Ma, Xiaojun; Park, Joo Young; Yang, Xuan
Informed by a constructivist-based, student-adaptive pedagogical approach, this study explores the benefits of teacher–learner discourse moves for the mathematics learning of students with learning disabilities (LD). During a constructivist teaching experiment for nurturing the multiplicative reasoning and problem solving of five third-grade students with school-identified LD, we analyzed the global trends and detailed dynamics of teacher–student interactions with statistical discourse analysis . We found that the teacher's discourse moves to support each individual student's problem solving helped engage them in mathematical reasoning, which improved their problem-solving performance. Thus, this study contributes to knowledge in the field of special education by (a) specifying ways in which discourse-oriented mathematics instruction can help each student with LD and (b) showcasing a novel statistical analysis of teacher–student discourse.